Fiscal Policy and Current Account Dynamics in the Case of Pakistan (The Pakistan Development Review, 2010)
The relationship between fiscal policy and the current account has long attracted interest among academic economists and policymakers after introduction of the standard intertemporal model of the current account by Sachs (1981) and its extension by Obstfeld and Rogoff, (1995) in open economy macroeconomics. There are two major strands of the current account literature Mundell-Fleming [Mundell (1968) and Fleming (1967)] and Ricardian equivalence [Barro (1974, 1989)] to explain such variations in the deficits. According to Mundell-Fleming model budget deficits cause current account deficits through stimulating income growth or exchange rate appreciation [Darrat (1988); Abell (1990); Bachman (1992) and Bahmani-Oskooee (1992)]. On the other hand, there is Ricardian view that the financing of budget deficits, either through reduced taxes or by issuing bond does not alter present value wealth of private households since both temporarily reduced taxes and issuance of bonds represent future tax liabilities [Kaufmann, et al. (2002); Evans (1989); Miller and Russek (1989); Enders and Lee (1990) and Kim (1995)]. The underlying reason is that the effects of fiscal deficits on the current account depend on the nature of the fiscal imbalance. For example, in a simple theoretical model in which Ricardian equivalence holds, a cut in lump sum taxes and the ensuing fiscal deficit would not affect the current account as the private savings increase will offset the fiscal deficit but investment will be unchanged. Conversely, a transitory increase in government spending will increase both the fiscal deficit and the current account deficit, a case of twin deficits. And a permanent increase in government spending will have no effects on the current account while its effects on the fiscal balance will depend on whether the extra spending is financed right away with taxes (in which case the fiscal balance is unchanged) or whether it is financed with debt (future taxes) in which case the fiscal balance worsens. Thus, fiscal deficit may or may not lead to current account deficits depending on the nature and persistence of the fiscal shock. There is also a third scenario relate to Recardian view that portrays the possibility of negative relationship between the deficits where, for example, output shock give rise to endogenous movements and two deficits are divergent.